ClC-5 chloride channel and kidney stones: what is the link? - I.V. Silva; M.M. Morales; A.G. Lopes (Brazilian Journal of Medical and Biological Research, 2001)
Nephrolithiasis is one of the most common diseases in the Western world. The disease manifests itself with intensive pain, sporadic infections, and, sometimes, renal failure. The symptoms are due to the appearance of urinary stones (calculi) which are formed mainly by calcium salts. These calcium salts precipitate in the renal papillae and/or within the collecting ducts. Inherited forms of nephrolithiasis related to chromosome X (X-linked hypercalciuric nephrolithiasis or XLN) have been recently described. Hypercalciuria, nephrocalcinosis, and male predominance are the major characteristics of these diseases. The gene responsible for the XLN forms of kidney stones was cloned and characterized as a chloride channel called ClC-5. The ClC-5 chloride channel belongs to a superfamily of voltage-gated chloride channels, whose physiological roles are not completely understood. The objective of the present review is to identify recent advances in the molecular pathology of nephrolithiasis, with emphasis on XLN. We also try to establish a link between a chloride channel like ClC-5, hypercalciuria, failure in urine acidification and protein endocytosis, which could explain the symptoms exhibited by XLN patients.